2016
DOI: 10.18865/ed.26.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Culturally Relevant Recruitment Strategies and Participant Interest, Enrollment and Generalizability in a Weight-loss Intervention for African American Families

Abstract: Objective: Culturally relevant recruitment strategies may be an important approach for recruiting ethnic minorities for interventions. Previous research has examined associations between recruitment strategies and enrollment of African Americans (AA), but has not explored more deeply the role of incorporating sociocultural values into recruitment strategies. Our current study explores whether sociocultural recruitment mediums were associated with demographics, interest and enrollment in a weight-loss intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…Another individual level enabling factor was participant altruism. Similar to a previous study among African Americans [27], our study found that participants were interested in participating in research because it may help the Filipino community in general.…”
Section: Discussionsupporting
confidence: 75%
“…Another individual level enabling factor was participant altruism. Similar to a previous study among African Americans [27], our study found that participants were interested in participating in research because it may help the Filipino community in general.…”
Section: Discussionsupporting
confidence: 75%
“…30,58,63e65,76 However, only one study compared the effects of different community engagement approaches on recruitment outcomes, finding that incorporating sociocultural values into recruitment was superior to nonsociocultural strategies and that recruitment through community partnerships led to the highest recruitment of target populations. 40 All of the studies described recruitment efforts; 20 studies described both recruitment and retention of research participants. 26,31e37,41,43,45,48,56e59,61,66,67,74 Minority groups recruited included black or African American (n¼46), 26e31,33,35e41,43e45,49e54,56,57,59e61, 64,68e73,77e80,82e86,89,91 Hispanic or Latino (n¼20), 27,32e35,37,39,42,47,48,58,63,65,67,70,78,80, 81,88,91 Asian (n¼6), 55,74e76,87,90 American Indian or Alaskan Native (n¼3), 32,47,66 and Native Hawaiian or other Pacific Islander (n¼2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Baseline data from 148 African American families participating in the on-going FIT for Weight Loss randomized-controlled trial [20,21] were included in the present study. Sociocultural mediums including community partnerships, community events, and culturally relevant ads were used as recruitment strategies to identify eligible families [66]. Families were eligible to participate if they had an African American adolescent between the ages of 11-16 years old who was overweight or obese (BMI ≥85th percentile for age and sex), a caregiver that was willing to participate, and internet access.…”
Section: Participantsmentioning
confidence: 99%